The drug treatment of premature ejaculation - Hisasue, Shin-ichi (Transl Androl Urol, 2016)
The management recommendation for both acquired premature ejaculation (APE) and lifelong PE (LPE) are similar, such as a behavioral/psychotherapy, a pharmacotherapy and a combination of these treatments. For the drug treatment for PE, gold standard is selective serotonin reuptake inhibitors (SSRIs) including dapoxetine or paroxetine. The drug treatment for PE is still developing and some new promising therapeutic options have been proposed. Topical anesthetics, tramadol, and alpha-1 blockers will be the next strategies of the drug treatment for PE in the future.